Nonisothermal particle modeling of municipal solid waste combustion with heavy metal vaporization - Mazza, German Delfor (2010)
A particulate model was developed for municipal solid-waste incineration in a fluidized bed combining solid-waste particle combustion and heavy-metal vaporization from the burning particles. Based on a simpler, isothermal version presented previously, this model combines an asymptotic-combustion model for carbonaceous-solid combustion and a shrinking-core model to describe the heavy-metal vaporization phenomenon in which the particle is now considered nonisothermal. A parametric study is presented that shows the influence of temperature on the global metal-vaporization process. The simulation results are compared to experimental data obtained with a lab-scale fluid bed incinerator and to the results of the simpler isothermal model. It is shown that conduction in the particle strongly affects the variation of the vaporization rate with time and that the present version of the model well fits both the shape of the plots and the maximum heavy-metal vaporization rates for all bed temperatures.